NUMERAL TO NUMERAL OF BALMIKI AND KUPIA: A MORPHOLOGICAL COMPARISON - Biswanandan Dash; Subrat Kalyan Pattanayak (Universitas Islam Sumatera Utara, 2023)
Numeral systems are the major counting methods found across languages. They are characterised by unique morphosyntactic structures to show numericity. The efficiency of communicating numbers is related to the morphological construction of numerals. These are also valuable sources for genetic classification. Besides, they play a vital role in establishing the antiquity of a cognate language. Peculiarly, the numeral systems of languages are the most vulnerable to elimination due to major or dominant languages. The quest in this article is to analyse the numeral morphology of Balmiki, a lesser-known language spoken in Odisha, and compare it with that of Kupia, a language spoken in Andhra Pradesh by the B/Valmiki community, to determine if their numeral structures are concealed or influenced by their encroaching languages. This study further contests a louder outbreak created during 2016-18 to ‘discover the Walmiki language’ by analysing a few unreliable numeral examples. In a series, this is the second study that compares and propounds conclusively to the fact that how these duo languages shed light on shared characteristics of numerals inherited or descended in other Indo-Aryan traditions from an etymological ancestor.